P49 The stromal compartment of hepatocellular carcinoma promotes the local differentiation of tolerogenic dendritic cells. (16th November 2010) - Bhatt, A; Curbishley, S M; Haughton, E L; Weston, C J; Blahova, M; Adams, D H
Abstract : Introduction: Hepatocellular carcinoma (HCC) stimulates an immune response but this fails to destroy the tumour which contains "stunned" effector T-cells and regulatory T cells (Tregs) that suppress antigen-specific responses. The number of Tregs in the tumour predicts survival in patients undergoing resection. The underlying mechanisms that suppress anti-tumour immunity are unknown. Because dendritic cells (DC) are critical for the induction and maintenance of immune activation we studied the effect of the tumour microenvironment on DC function in patients with HCC. We hypothesise that the tumour microenvironment (TM) modifies DC differentiation resulting in the suppression of anti-tumour immunity. Aim: In order to test this hypothesis we modelled the TM in vitro and studied its effect on the differentiation and function of DCs. Method: DCs isolated from HCC tumour cores and uninvolved human liver tissue were compared with human monocyte-derived DCs (MoDC) matured in tissue conditioned media (CM). DC function was studied in T cell activation assays and the effect of tumour on DC function modelled by co-culturing with either tumour tissue or tumour-derived fibroblasts. Results: Tumour-derived DCs had a tolerogenic phenotype (MHCIIlowCD86low) compared with DC isolated from matched uninvolved liver. This phenotype was recapitulated in vitro by culturing MoDCs in HCC CM after which levels of MHC II and CD86 were significantly lower than on MoDCs matured in matched non-tumour liver CM (p=0.001). Tumour-conditioned MoDCs induced significantly less naive T cell proliferation compared with MoDC matured in CM from uninvolved or inflamed liver tissue. Furthermore tumour-conditioned DCs generated significantly more CD4+CD25+FOXP3+ Tregs (p=0.01) and IL10producing T-cells (p=0.01). To determine the cell type responsible for this effect naive MoDCs were co-cultured with fibroblasts (-smooth muscle actin+vimentin+CD90+) isolated from either tumour cores or uninvolved liver. DCs conditioned by tumour fibroblasts developed a tolerogenic phenotype (MHCIIlowCD86low) and the ability to induce Tregs. Culturing MoDCs in tumour stroma CM had a similar effect implicating soluble factors. Part of this effect was IL-6-dependent because depletion of IL-6 from tumour-fibroblast CM abolished the ability to generate tolerogenic DC. Conclusion: Tumour associated fibroblasts in HCC contribute to an IL-6-rich TM that drives differentiation of tolerogenic DCs. These DCs generate immunosuppressive Tregs and IL-10 secreting T-cells which inhibit anti-tumour immunity. Inhibition of IL-6 or downstream STAT-3 signalling could prevent tumour-associated immunosuppression and hence be an important immunotherapeutic strategy in HCC.